Dual phase reinforced CuCrZr alloy: Synergistic improvement of mechanical properties and corrosion resistance via metallic glass and rare earth oxides - Jie Chen; Weizong Bao; Hongmei Chen; Ning Ding; Xinxin Yang; Bohua Yu; Tao Hong; Zeyun Cai; Guoqiang Xie (Materials & Design)
The interfacial adhesion plays a key role in the mechanical, electrical and corrosion properties of composites. For the high strength-conductive CuCrZr/CuZrAl metallic glass composites, the interface between the two phases suffered from excessive oxide film due to the strong affinity to oxygen of the Zr element. The rare earth particles Sc/Y are introduced into CuCrZr-30 wt% CuZrAl metallic glass composites to control the interface oxide layer and promote the properties of the composites. The incorporated Sc/Y particles trigger significant grain refinement effect in the CuCrZr matrix, which is enhanced with the increasing Sc/Y content. Sc particles offers a more pronounced grain refinement effect compared to the Y particles, yielding a more positive impact on the strength of the composites. With 1.5 wt% Sc added, the strength of the composites reaches up to 1180 MPa, while maintaining 24.8 % IACS. Moreover, the in-situ generation of rare earth oxides (Sc2O3/Y2O3) effectively enhances the interface bonding between the CuZrAl metallic glass and the CuCrZr matrix, improving the corrosion resistance of composites. This suggests a viable approach to construct dual-phase multiscale structure in the Cu-based composites with optimized interfaces and multiple strengthening effect.